The Influence of Principal's Participative Leadership Style and Work Climate on Public Middle School Teacher Performance - Yudela Arina; Yuni Revita; Nurhizrah Gistituati; Rusdinal Rusdinal (research, training and philanthropy institution Natural Aceh, 2023)
There is still a phenomenon in the field where some teachers lack discipline in teaching, and their motivation fluctuates, thus lowering the quality of their performance. Teachers' work or organizational climate is also seen as less favourable, possibly due to a lack of effective communication and feelings of jealousy towards colleagues. Indeed, this will impact the teachers' emotional state, which in turn affects their performance. Leadership participation is needed in such conditions. This study is field research with a quantitative approach. The research subjects consisted of 30 teachers. The research findings conclude that: a) there is an influence of the principal's participative leadership style on the performance of middle school teachers, b) there is an influence of the work climate on the performance of middle school teachers, c) there is a combined influence of the principal's participative leadership style and the work climate on the performance of middle school teachers, and d) the simultaneous influence of the independent variables, the principal's participative leadership style, and the work climate, on the dependent variable, the performance of middle school teachers, accounts for approximately 90.1% and is influenced by other unmentioned variables. The implications of this research can serve as a guideline for school principals to implement a participative leadership style that supports teachers in developing their performance and creates a positive and conducive work climate to enhance teachers' performance in schools.